2002
DOI: 10.4049/jimmunol.169.1.476
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Transepithelial Migration: Evidence for Sequential, Contact-Dependent Signaling Events and Enhanced Paracellular Permeability Independent of Transjunctional Migration

Abstract: Active migration of polymorphonuclear leukocytes (PMN) through the intestinal crypt epithelium is a hallmark of inflammatory bowel disease and correlates with patient symptoms. Previous in vitro studies have shown that PMN transepithelial migration results in increased epithelial permeability. In this study, we modeled PMN transepithelial migration across T84 monolayers and demonstrated that enhanced paracellular permeability to small solutes occurred in the absence of transepithelial migration but required bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 54 publications
(47 reference statements)
4
75
0
Order By: Relevance
“…The TER of WT monolayers decreased dramatically upon addition of neutrophils ( Figure 8A), as described previously (42). Interestingly, although respective WT and KD HCA7 monolayers were morphologically similar by light microscopy, TER was severely reduced by p120 KD, irrespective of neutrophil presence ( Figure 8A).…”
Section: Figuresupporting
confidence: 55%
See 2 more Smart Citations
“…The TER of WT monolayers decreased dramatically upon addition of neutrophils ( Figure 8A), as described previously (42). Interestingly, although respective WT and KD HCA7 monolayers were morphologically similar by light microscopy, TER was severely reduced by p120 KD, irrespective of neutrophil presence ( Figure 8A).…”
Section: Figuresupporting
confidence: 55%
“…To clarify the role of the epithelial barrier, as apposed to other events linked to p120 ablation (e.g., neutrophil behavior), we generated p120 knockdown (KD) HCA7 cells and evaluated the in vitro effect of p120 KD on several relevant phenotypes (Figure 8). WT (pLentiLox-GFP [pLL-GFP]) and p120 KD (pLentiLox-hp120i-GFP [pLL-hp120i-GFP]) HCA7 cells were plated on neutrophil permeable (3-μm pore size) filters, as described by Edens et al (42). Neutrophils were then added to the basal side with chemoattractant (fMLP) on the apical side.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We have further observed an increase in epithelial permeability (reduced barrier function) when PMN contact the epithelial basolateral surface in the presence of a transepithelial gradient of fMLP (39). This observation suggests that active signaling events between PMN and epithelial cells at early stages of the transepithelial migration, although independent of ␤ 2 integrins, may serve to facilitate PMN transmigration.…”
Section: Cell Surface Events During Transepithelial Migrationmentioning
confidence: 60%
“…Direct effects of PMNs on epithelial cell function appear to be mediated both by cell-cell contact and by release of factors that initiate subsequent signaling events. For example, we have recently shown that as sub-epithelial PMNs enter the paracellular space in response to a lumenal chemoattractant, epithelial permeability increases through undefined mechanisms that are independent of junctional disruption (Edens et al 2002). In addition, as PMNs migrate across the colonic epithelium, PMN-derived 5'-AMP (Madara et al 1993) is converted to adenosine which activates electrogenic chloride secretion and passive water movement into the lumen (Strohmeier et al 1995(Strohmeier et al , 1997.…”
Section: Leukocyte-epithelial Interactions and Disease Pathophysiologymentioning
confidence: 99%